City & suburban gardens : front yards, back yards, terraces, rooftops, window boxes - Riker, Tom. (London, United Kingdom : Prentice-Hall International Inc., 1977)
A garden book should not only be used as a decoration for the table, but also as something to carry into the garden along with other tools. A book on garden planning and garden building can help you a great deal and also save you money-if you have the right questions to ask.
Book One. The basics -- Book Two. The plants -- Book Three. The garden -- The back of the book. A word-toolshed.
Keywords: GARDENING